To the gates of hell - Nix, David (Nix, David. Jake Paynter series, 2022)
Jake Paynter escaped the noose, but the price of salvation is pain. Since reluctantly accepting the marshal's job at South Pass City, Jake's life has become an unending run of solving other people's problems. When outlaw boss Dutch van Zandt and his ruthless band mount a campaign of mayhem in Jake's corner of the Wyoming Territory, Jake learns that Lucien Ashley, his persistent adversary, may be aiding the criminals to expand his burgeoning cattle fortune. The fact that Lucien is the brother of Rosalyn, a woman Jake admires, complicates matters. Determined to thwart van Zandt and Lucien, Jake recruits a posse of old friends and former platoon mates that puts the outlaw gang on the run. When Lucien betrays van Zandt, the outlaw leader loots Jake's town and takes Rosalyn and four children captive. With friends few and enemies in abundance, Jake must thread a harrowing needle to run down van Zandt in the rugged Wyoming wilderness and save Rosalyn and the children without ending up in a shallow grave.